Experience in Documenting and Visualizing Small Artifacts: a case study of Palmyrene tesserae from the Pushkin State Museum of fine arts collection - Maria G. Bodrova; Alexey K. Lyavdansky (Археология евразийских степей)
The paper presents the experience of 3D modeling (photogrammetry) of nine small-sized archaeological artifacts from the collection of the Pushkin State Museum of Fine Arts. The objects of study are tesserae with shallow impressions and signs of wear, which required the use of macro photography and specialized image processing algorithms to achieve high detail. The technical aspects of photography are examined, including the use of a camera with a macro lens and motorized rails to stabilize the shooting process. The article also provides an analysis of model processing methods, such as the application of the MSII algorithm to improve the legibility of inscriptions and images. Challenges encountered when modeling objects with damaged surfaces are discussed, along with proposed solutions to enhance visualization quality. The study's results demonstrate new possibilities for creating highly detailed models for scholarly work with museum artifacts.